Nilai-Nilai Advensitas Mahasiswa Pendidikan Agama Islam Dalam Menyelesaikan Skripsi Di Universitas Sains Al-Qur’an Wonosobo - El Syam, Robingun Suyud; Al-Halim, A. Adibudin (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2025)
This study aims to analyze the adventitious values of Islamic religious education students in completing their theses at the Al-Qur'an Science University in Wonosobo. The study is a descriptive qualitative study, using listening techniques with advanced notes. The subjects of this study were 73 subjects taken using a purposive sampling technique. The results of the analysis concluded that Islamic religious education students in completing their theses at the Al-Qur'an Science University in Wonosobo have adventitious values (fighting power) which is a person's ability to face obstacles and challenges in completing the thesis. These values include feeling empowered, steadfast, optimistic, and having the ability to survive in the face of difficulties. This study has theoretical implications, namely dissecting the flow of adventitious intelligence in detail, then analyzing life lessons where positive things are used as lessons to be emulated. The practical implication is that this study can be used as a reference for students to provide life education in working on theses. The study provides recommendations for academics who are interested in studying adventitious intelligence, as well as the need for closer mentoring for students who are working on theses.